2021
DOI: 10.1007/s00216-021-03745-2
|View full text |Cite
|
Sign up to set email alerts
|

Two-photon fluorescence lifetime for label-free microfluidic droplet sorting

Abstract: Microfluidic droplet sorting systems facilitate automated selective micromanipulation of compartmentalized micro- and nano-entities in a fluidic stream. Current state-of-the-art droplet sorting systems mainly rely on fluorescence detection in the visible range with the drawback that pre-labeling steps are required. This limits the application range significantly, and there is a high demand for alternative, label-free methods. Therefore, we introduce time-resolved two-photon excitation (TPE) fluorescence detect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 44 publications
(56 reference statements)
0
8
0
Order By: Relevance
“…were not yet able to reach the single-cell level and were limited to low sorting frequencies of 1-2 Hz. 31,32 This is now targeted in the current study to distinguish and sort living and dead cyanobacterial cells. We choose Synechocystis sp.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…were not yet able to reach the single-cell level and were limited to low sorting frequencies of 1-2 Hz. 31,32 This is now targeted in the current study to distinguish and sort living and dead cyanobacterial cells. We choose Synechocystis sp.…”
Section: Introductionmentioning
confidence: 99%
“…This is especially true for the field of high-throughput sorting, which is limited by the ability to determine fluorescence lifetimes at high rates. In our previous works 31,32 we developed an approach for label-free fluorescence lifetime activated droplet sorting and showed its potential to distinguish model substances. In this study, we also demonstrated the suitability of the approach for cell sorting of yeast cells using two-photon excitation, but we were not yet able to reach the single-cell level and were limited to low sorting frequencies of 1–2 Hz.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…), and produces lower throughputs (max 50 Hz sorting rate). [29][30][31][32][33] Until now, it is considered difficult, if not impossible, to overcome the Poisson limit of droplet microfluidics with an easy and versatile solution.…”
Section: Introductionmentioning
confidence: 99%
“…The maximal sorting throughput (based on detection methods such as image processing, Raman spectrum, UV-vis spectrum etc.) is around 300 cell-loaded droplets per minute [29][30][31][32][33]. Currently, there is not a general solution for high throughput, label-free, and deterministic single cell encapsulation into droplets.…”
Section: Introductionmentioning
confidence: 99%